Availability of timber housing construction techniques in Brazil - De Araujo, Victor A.; Gutierrez-Aguilar, Carlos M.; Cortez-Barbosa, Juliana [UNESP]; Gava, Maristela [UNESP]; Garcia, Jose N. (Univ Catolica Colombia, Fac Psicologia, 2019)
This paper analyzes the representativeness of timber housing in Brazil, identifying the percentage of construction techniques offered by each evaluated company. Percentages that evidence the frequency of use of wooden building techniques were measured using two methods applied in the companies: survey through face-to-face interviews with owners and data search on their websites. The survey through interviews evaluated 107 Brazilian companies, while the data search included 207 companies, obtaining 50.95% and 98.57%of the estimated population, respectively. methods showed a similar scenario. Interviews evidenced higher application costs. Contemporary techniques are available in more than 90% of Brazilian constructors. Houses with nailed horizontal boards and houses with horizontal wooden boards between columns were offered the most.
Keywords: Timber architecture in Brazil; wood structures; plant materials; construction materials; construction systems; timber housing